Tetramethylammonium Iodide (TMAI)‐Promoted Sulfenylation/Annulation of Enaminones with Thiosulfonates. Issue 2 (11th January 2022) - Zhang, De‐Run; Hu, Lin‐Ping; Yang, Cai‐Yun; Li, Xia; Teng, Ming‐Yu; Liu, Bo; Huang, Guo‐Li
Abstract: A highly efficient and eco‐friendly method for the tetramethylammonium iodide‐mediated sulfenylation/annulation of enaminones using thiosulfonates as the sulfenyl source was described under open‐air, metal‐, and oxidant‐free conditions. This method provides an alternative way of constructing C−S bonds, affords various substituted sulfenylated chromones in moderate to good yields, and shows broad substrate scope, and good functional group tolerance. Abstract : Tetramethylammonium iodide (TMAI)‐promoted sulfenylation/annulation of enaminones using widely accessible thiosulfonates as the sulfenyl source was described under metal‐ and oxidant‐free conditions. These methods provide an alternative and facile synthetic route to access a series of 3‐sulfenylated chromones in moderate to good yields. This is a useful, time‐efficient, and scalable procedure for the construction of C(sp 2 )−S bonds.